Legal Protection for Sellers in Cash on Delivery Schemes: Analysis of Consumer Rights Abuse in Electronic Commerce Transactions - Latif Argani; Susilo Wardani; Yusuf Saefudin (Journal of Law and Policy Transformation, 2025)
The development of information technology has led to a shift from conventional transactions to electronic commerce, including the widespread use of Cash on Delivery (COD) systems on marketplace platforms. Although COD provides a sense of security for consumers, it also creates legal risks for sellers, particularly when buyers abuse the product return mechanism. This study examines the legal protection available to online sellers against the misuse of COD returns, using a case example of a sports retail business in Banyumas, including Planet Shoes Banyumas. This research applies a normative legal method based on the Indonesian Civil Code (KUHPerdata), particularly the provisions governing sale and purchase agreements (Articles 1457–1540), the principle of good faith (Article 1338 paragraph 3), the principle of balance between contractual parties, and the concept of breach of contract (Article 1243). The act of returning goods that have been replaced with different items constitutes a breach of contract, which gives sellers the legal right to demand performance or compensation. The findings indicate that the enforcement of sellers’ rights is often constrained by limited evidence, incomplete consumer data, and the restricted role of third parties such as marketplace platforms and courier services, whose responsibilities are not comprehensively regulated in electronic contracts. This study recommends strengthening legal protection through clearer contractual clauses, proper documentation of product conditions, and technical verification mechanisms during the return process. The findings are expected to contribute to the development of civil law in the context of digital transactions and to provide practical guidance for business actors using COD systems in order to promote more balanced contractual relationships.